PEMENUHAN HAK NAFKAH ANAK AKIBAT PERCERAIAN DI KECAMATAN ULU TALO KABUPATEN SELUMA PERSPEKTIF HUKUM ISLAM - Sari, Eni Putri (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: The formulation of the research problem is: 1) How is the fulfillment of children’s livelihood rights due to divorce in Ulu Talo District, Seluma Regency? 2) How is the implementation of the fulfillment of children’s livelihood rights due to divorce in Ulu Talo District, Seluma Regency, from a Islam law perspective?. The type of research is field research (field research). Data collection uses observation, interview and documentation techniques which are analyzed based on reading and quoting information. This study concludes that: 1) Fulfillment of the Child’s Livelihood Rights Due to Divorce In Ulu Talo Subdistrict, Seluma Regency, the fulfillment of the responsibility to meet the needs of the child after divorce, only the mother of the child (ex-wife) and assisted by the mother’s parents in mutual cooperation , by the way the mother works and has a business. 2) According to the Compilation of Islamic Marriage Law on Child Care Article 156 (d) in the event of a divorce “All hadhanah costs and child maintenance are the responsibility of the father according to his ability, at least until the child is an adult able to take care of himself (21 years old). Keywords: Children’s Livelihood Rights Due to Divorce. Abstrak: Rumusan masalah penelitian ini adalah : 1) Bagaimana pemenuhan hak nafkah anak akibat perceraian di Kecamatan Ulu Talo Kabupaten Seluma? 2) Bagaimana pelaksanaan pemenuhan hak nafkah anak akibat perceraian di Kecamatan Ulu Talo Kabupaten Seluma perspektif hukum Islam?. Jenis Penelitian adalah penelitian lapangan (field reseacrh). Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi yang di analisa berdasarkan dengan membaca dan mengutif informasi. Penelitian ini menyimpulkan bahwa: 1) Pemenuhan Hak Nafkah Anak Akibat Perceraian Di Kecamatan Ulu Talo Kabupaten Seluma, pemenuhan tersebut yang menanggung untuk memenuhi kebutuhan anak setelah bercerai, hanya ibu dari anak (mantan istri) dan dibantu oleh orangtua dari pihak ibu secara bergotong-royong, dengan cara ibu bekerja dan mempunyai usaha. 2) MenurutKompilasi Hukum Islam Perkawinan tentang Pemeliharaan Anak Pasal 156 (d) jika terjadinya perceraian “Semua biaya hadhanah dan nafkah anak menjadi tanggung jawab ayah menurut kemampuannya, sekurangkurangnya sampai anak tersebut dewasa dapat mengurus diri sendiri (21 tahun). Kata Kunci: Hak Nafkah Anak Akibat Perceraian